Penerapan Model PAKEM Pada Kursus Bimbingan Belajar Berbasis Tematik Gratis di SDN 175795 Lobutangga - Narambean Simanjuntak; Diana Sihombing; Serepina Lubis; Winda Josefina Simamora; Sugita Sonya Simanjuntak; Lolly Biopanni Simanjuntak; Christina Natalina Saragi (Utan Kayu Publishing, 2022)
The goal of implementing this community service program (PkM) is to use an active, creative, effective, and enjoyable learning model (PAKEM) in thematic-based learning. Based on first observations made on January 29, 2022 utilizing the direct review and interview approach (to the principal), the school still has a state C accreditation status using the 2013 curriculum. At the school, there are some students who cannot write, read, or count (Calistung), and there are also some students who can only count, and because of the Covid-19 pandemic situation, the school has implemented online school learning to avoid the spread of the Covid 19 Virus, but students do not have communication tools that support online learning, and students' learning time is reduced due to their inability to purchase data packages. The goal of conducting this PkM activity is to reach around 80 persons, with pupils from SD N 175795 Lobutangga being prioritized. The implementation period lasts one month, during which time free tutoring for all courses is provided. Following the installation of PkM, around 75% of pupils who could not read or spell previously began to read and spell better than before. Students are more eager to learn since the manner we utilize captures their interest. Students are more likely to accept learning at school if it has already been taught during tutoring, and teachers are more likely to teach some topic if it has previously been taught during tutoring